Construction site on Christmas night - Rinker, Sherri Duskey (Rinker, Sherri Duskey. Goodnight, goodnight, construction site., 2018)
It is Christmas Eve, and all the construction vehicles are finishing up work on the site, and when they leave they find that there is a special present waiting for each of them.